2001
DOI: 10.1053/ejvs.2000.1293
|View full text |Cite
|
Sign up to set email alerts
|

The Lack of Cardiovascular Risk Factor Management in Patients with Critical Limb Ischaemia

Abstract: only a minority of patients operated on for CLI were receiving adequate cardiovascular risk factor modification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 17 publications
2
15
0
5
Order By: Relevance
“…15,[21][22][23][24][25][26][27][28][29][30] Even in ideal conditions, the success rates in reaching national targets are dismal. In a study of a socioeconomically homogeneous, multiethnic, well-educated population with comprehensive medical benefits, Ͼ80% failed to achieve blood pressure control despite full access to and active participation in the community's medical care system.…”
Section: Discussionmentioning
confidence: 99%
“…15,[21][22][23][24][25][26][27][28][29][30] Even in ideal conditions, the success rates in reaching national targets are dismal. In a study of a socioeconomically homogeneous, multiethnic, well-educated population with comprehensive medical benefits, Ͼ80% failed to achieve blood pressure control despite full access to and active participation in the community's medical care system.…”
Section: Discussionmentioning
confidence: 99%
“…30 In patients with PAD, a recent study described that 35% of all patients (and only 30% of those with lower-extremity disease) were on a lipid-lowering agent, 31 whereas yet another investigation found that only 5% of their patients with critical lower-extremity vascular disease received lipid-lowering treatment. 32 There is also evidence that patients with PAD receive lipid-lowering treatment less often than patients with CAD. 33 We found a very high variability for the use of statins between the participating departments.…”
Section: Discussionmentioning
confidence: 99%
“…2,[11][12][13][14][15] For example, in one study, lipid-lowering therapy was prescribed for 70% of patients with both PAD and coronary artery disease, but for only 35% those with isolated PAD. 12 This may reflect a lack of randomized controlled trials in the PAD population.…”
Section: Discussionmentioning
confidence: 99%
“…North American and European studies from the 1990s and early 2000s suggest that less than 50% of patients received appropriate vascular protection. [11][12][13][14] In the most recent and largest study to date regarding appropriate vascular protection in PAD, prescribing rates were below 40% for statins, ACE inhibitor or ARB, and ASA (considered individually), despite the evidence suggesting that most patients with PAD would benefit from these therapies. 13 The study reported here was undertaken to investigate pharmacotherapy provided to patients with concurrent diabetes and PAD and the prescribing trends for cardiovascular agents used in this population.…”
Section: Introductionmentioning
confidence: 99%